2018
DOI: 10.5751/es-09995-230204
|View full text |Cite
|
Sign up to set email alerts
|

To log or not to log: local perceptions of timber management and its implications for well-being within a sustainable-use protected area

Abstract: ABSTRACT. Our research explores local perspectives of a recent and controversial shift in conservation and development strategies in the Brazilian Amazon whereby legal timber commercialization is being pioneered in select extractive reserves, which are a type of comanaged sustainable-use protected area. To understand how this initiative might affect well-being, we documented perceptions of reserve residents about a legal logging project and factors that influenced their decision to participate or not participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…The decision of forest owners to harvest/not harvest timber is guided by many factors [12,[30][31][32]. Among many variables, timber price, forest size, distance to property, ownership objectives, policy awareness, membership in a forest organization, and socio-economic factors such as age, gender, education, income, and net wealth have been emphasized in the following studies [22,31,[33][34][35]. However, their reported magnitude and statistical significance on timber harvesting intentions and intensities are not consistent across studies [30,36].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The decision of forest owners to harvest/not harvest timber is guided by many factors [12,[30][31][32]. Among many variables, timber price, forest size, distance to property, ownership objectives, policy awareness, membership in a forest organization, and socio-economic factors such as age, gender, education, income, and net wealth have been emphasized in the following studies [22,31,[33][34][35]. However, their reported magnitude and statistical significance on timber harvesting intentions and intensities are not consistent across studies [30,36].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Gross-Camp (2017) found that community forestry in Tanzania had limited impact on household wealth, but that community members still supported the initiative because of greater governance over and pride in their natural resources. In Brazilian extractive reserves, communities sold the rights to extract their timber, engaging in very little of the actual activity (Cooper and Kainer 2018). The authors found both positive (social and financial) and negative (environmental and governance) impacts of these projects, with variations in perceptions of these across gender.…”
Section: Approaching a Brave New Worldmentioning
confidence: 99%
“…However, the timber management carried out in CMER-Xapuri had little local participation in operations, and even generated controversy, perhaps suggesting premature implementation (ICMBio-MMA, 2016). Similarly, in CMER-Brasiléia/Epitaciolândia, participation in pre-harvest activities was generally limited to attending a handful of meetings, and many residents expressed frustration with government (vs. resident) control to authorize timber management, harvest, and commercialization, with little local input in these decisions (Cooper & Kainer, 2018).…”
Section: Cooperfloresta Developed the Pmfs And Annualmentioning
confidence: 99%
“…Participants were primarily motivated by the additional income, and indeed, these households showed greater financial need compared to non-participating households. Meanwhile, non-participants argued that the quoted price of timber (R$60/m 3 ) was unacceptably low (Cooper & Kainer, 2018). In terms of addressing clandestine logging in the CMER, the legalization of low-intensity logging was perceived as important among several project supporters; legalization would grant secure and legal access to needs-based timber income that may otherwise be sought reluctantly through informal means (Cooper & Kainer, 2018).…”
Section: Cooperfloresta Developed the Pmfs And Annualmentioning
confidence: 99%
See 1 more Smart Citation